Removal of Methylene Blue in aqueous solutions by Electrocoagulation process: Adsorption, Kinetics, studies - Assémian, Alain Stéphane; Kouassi, Konan Edmond; Adouby, Kopoin; Drogui, Patrick; Boa, David (European Journal of Chemistry, 2018)
The purpose of this study is to understand the mechanism driving the removal of methylene blue through electrocoagulation process. Experiments were carried out using iron as anode and cathode in a batch electrochemical cell operated in a monopolar configuration. The effects of operating parameters (initial pH, current density, initial dye concentration and energy consumption) on the removal of methylene blue from solution were investigated. The results showed that the optimum removal efficiency of 93.2% was achieved for a current density of 9.66 mA/cm2, optimal pH of 8±0.01 with a specific energy consumption of 7.451 kWh/m3. Afterwards, first and second-order rate equations were successively applied to study adsorption kinetics models. On top of usual correlation coefficients (r2), statistical test Chi-square (χ2) were applied to evaluate goodness of fit and consequently find out the best kinetic model. Results showed that MB adsorption process onto iron hydroxides formed in aqueous solution during electrocoagulation treatment followed a second-order kinetic.